Diffusion-Weighted and Conventional MR Imaging Findings of Neuroaxonal Dystrophy - Sener, R. Nuri (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Neuroaxonal dystrophy is a rare progressive disorder of childhood characterized by mental deterioration and seizures. The diffusion-weighted and conventional MR imaging findings are reported for six cases.METHODS: Six patients aged 19 months to 9 years with proved neuroaxonal dystrophy (one with the infantile form, five juvenile forms) underwent imaging at 1.5 T. Echo-planar diffusion-weighted images were acquired with a trace imaging sequence in five patients and with a three-gradient protocol (4000/110) in one. Images obtained with a b value of 1000 s/mm2 and corresponding apparent diffusion coefficient (ADC) maps were studied. ADCs from lesion sites and normal regions (pons and temporal and occipital lobes) were evaluated.RESULTS: A hyperintense cerebellum (a characteristic of the disease) was evident on fluid-attenuated inversion recovery images in all cases. Four patients had associated cerebral changes. Diffusion-weighted images, especially ADC maps, showed an elevated diffusion pattern in the cerebellum in the five juvenile cases (normal images at b = 1000 s/mm2, ADCs of 1.30–2.60 × 10−3 mm2/s). A restricted diffusion pattern was evident in the infantile case (hyperintensity at b = 1000 s/mm2, low ADCs of 0.44–0.55 × 10−3 mm2/s). ADCs were normal in the pons and temporal and occipital lobes (0.64–1.00 × 10−3 mm2/s).CONCLUSION: An elevated cerebellar diffusion pattern is a predominant feature of juvenile neuroaxonal dystrophy. Coexistent elevated and restricted diffusion patterns were evident in different brain regions in different forms of the disease. Dystrophic axons likely account the restricted diffusion, whereas spheroid formation (swelling) and abnormal myelination result in elevated diffusion.